Factors Influencing Hundred's Hot Chicken Customer Satisfaction and its Impact on Consumer Loyalty - Batara Surya Kalbu Hidayat; Harianto Harianto; Asep Taryana (Journal of Social Research, 2023)
The marketing mix evaluation (7P) that has been carried out by Hundred's Hot Chicken plays a very important role in efforts to develop its marketing strategy. The questionnaire in this research was conducted on 200 respondents who were included in the research criteria, namely that respondents were consumers who had visited the company at least once or more. The results of this research found that products have a significant effect on consumer satisfaction and consumer loyalty, followed by the people dimension which has a significant effect on consumer satisfaction and consumer loyalty and consumer satisfaction has a significant effect on consumer loyalty. Hundred's Hot Chicken's Customer Satisfaction Index (CSI) value is 77.04 and the Customer Loyalty Index value is 80.31. The results of the Importance Performance Analysis (IPA) analysis show the attributes whose performance needs to be improved to increase consumer satisfaction. These attributes are Food Cleanliness, Prices, Employee Patience, Employee Alertness and Nameplates. Hundred's Hot Chicken is a restaurant that has a distinctive food taste, Hundred's Hot Chicken requires quality control over the taste of its products so that the taste does not change in the minds of consumers and the need to pay attention to employee uniforms to show the restaurant's identity and also the intensity of uniform use can increase consumer satisfaction. Hundred's Hot Chicken and increase employee confidence and pride so that consumers will feel satisfied and loyal to Hundred's Hot Chicken.